(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to deeply investigate nursing students’ perceptions of social support through their participation in community activities. Methods: A cross-sectional mixed-method study was conducted with 132 third- and fourth-year nursing students from Pham Ngoc Thach University of Medicine who participated in pandemic control in 2021. Data were collected in 2022 via self-administered questionnaires, in-depth interviews, and focus group discussions. Descriptive statistics and content analysis were applied. Results: On average, 85.5% of students reported receiving social support, with the highest support from friends and medical staff (94.7%). Adequate material support was reported by 73.5%. However, 40.9% experienced opposition when volunteering. Qualitative data revealed that while students received both emotional and material support, some limitations remained, such as inconsistent support and weak connections. Conclusion: Students had a generally positive perception of social support during community activities. It is essential to strengthen the connection among the school, students, families, and the community, and to build comprehensive, timely support mechanisms to enhance effectiveness and professional engagement.